(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The Peipsi-Pskov Lake is the largest freshwater body in Europe, ranking fourth in area and fifth in volume. It is characterized by shallow water and a high level of trophy. The water in the lake is poorly mineralized and has little transparency due to suspended sediments and the development of plankton. Phytoplankton acts as a primary link in trophic chains, quickly reacts to changes in the aquatic environment and serves as a convenient object in monitoring studies.The average concentrations of total nitrogen in the lake during the observation period were in the range of 525-818 µg/dm3. The content of ammonium, nitrate, and nitrite nitrogen in the samples was mostly below the detection limits. The values of total phosphorus varied from 20 µg/dm3 to 54 µg/dm3, and its concentrations were lower than the sensitivity of the method during the flood recession.The maximum values of total nitrogen and phosphorus were recorded in August: in Lake Peipsi - 1.12 mg/dm3 and 0.09 mg/dm3, in Lake Pskov - 1.59 mg/dm3 and 0.14 mg/dm3, respectively. BOD5 values ranged from 1.96 mg/dm3 in autumn to 4.26 mg/dm3 in summer.During the growing season of 2020, 244 species taxa of phytoplankton from 8 phylums were identified in the Peipsi-Pskov Lake: Chlorophyta, Bacillariophyta, Cyanobacteria, Chrysophyta, Euglenophyta, Cryptophyta, Dinophyta and Xanthophyta. Floristic complex was characterized as сhlorophyta-diatom-cyanobacterial.The number of phytoplankton varied between 2.1 and 16.2 million cells/l depending on the season. The average number was 7.6 million cells/l. The biomass values ranged from 0.9 g/m3 to 3.6 g/m3. The average biomass was 2.3 g/m3.According to the ecological and geographical characteristics of the lake, widespread freshwater forms of microalgae predominated, preferring stagnant-flowing, slightly alkaline waters.Saprobiological analysis showed that the waters of the Peipsi-Pskov Lake were classified as moderately polluted, class III of water purity quality.